Pedunculoside attenuates pathological phenotypes of fibroblast-like synoviocytes and protects against collagen-induced arthritis. (3rd September 2019) - Ma, X; Chen, G; Wang, J; Xu, J; Zhao, F; Hu, M; Xu, Z; Yang, B; Guo, J; Sun, S; Liu, M
Abstract : Objectives : The discovery of alternative and well-tolerated anti-arthritic drugs, especially from natural products, is becoming an area of active research. Pedunculoside (PE) is a novel triterpene saponin extracted from the dried bark of Ilex rotunda Thunb. Limited published papers have reported its pharmacological properties, including anti-inflammatory, anti-myocardial ischaemia, anti-liver injury, and hypocholesterolaemic activities. However, the effect of PE on rheumatoid arthritis (RA) remains unknown. Here, we investigated the anti-arthritic effect of PE in both in vitro and in vivo models. Method : The inhibitory effects of PE on proliferation, migration, and production of inflammatory mediators in primary fibroblast-like synoviocytes (FLSs) were examined by a 5-ethynyl-2ʹ-deoxyuridine incorporation assay, wound-healing assay, and real-time polymerase chain reaction, respectively. Cellular signalling mechanisms were analysed by Western blot. The in vivo studies were performed using a collagen-induced arthritis (CIA) rat model. Multiple methods, including arthritis scoring, enzyme-linked immunoassay, radiography, and histopathological assessment, were used to evaluate the therapeutic effects of PE on CIA rats. Results : The in vitro studies revealed that PE significantly inhibited proliferation and migration of FLSs. PE also decreased the production of pro-inflammatory cytokines, including interleukin-1β (IL-1β), IL-6, IL-8, and tumour necrosis factor-α (TNF-α). Western blot results suggested that PE suppressed TNF-α-stimulated activation of p38 and extracellular signal-regulated kinase. The in vivo studies showed that PE treatment significantly inhibited synovial inflammation and bone destruction in CIA rats. Conclusion : These results demonstrate that PE exerts an inhibitory role in FLSs and CIA rats, and therefore may have therapeutic value for the treatment of RA.